Autonomy for Robots: Design and Developmental Challenges (Keynote Address). (2016) - Thondiyath, Asokan
Abstract: Autonomy for robots is one of the key requirement in any field robotic applications. Design and development of autonomous robots raises many challenges to the engineers and full autonomy for robots is still an unfinished job. In this key note address, some of the design challenges and implementation issues will be presented. Along with this, the design of an autonomous underwater robot for surveillance application will be presented as a case study.